Effect of Manual Traction on Patients with Cervical Spondyloarthrosis - Indah Permata Sari Sari; Faridah (Indonesian Journal of Advanced Research, 2022)
Cervical spondyloarthrosis is a condition where there are degenerative changes in the intervertebral joints of the spine and discs which result in degenerative changes in the synovial joints. Manual traction is a technique of holding the cervical segment manually and by pulling the body's resistance to increase the distance between the joints in the cervical segment and provide stimulus to the mechanoreceptors. This study aims to see the effect of pre and post on manual traction in cervical spondyloarthrosis patients. This study used a pre-experimental design with a one-group pre-post test design. The sampling technique used purposive sampling method with a sample of 10 people with neck pain. Data analysis techniques using the Wilcoxon test. The research instrument used was a visual analogue scale. Wilcoxon test results before and after treatment showed p <0.05. The results show that there is an effect of reducing pain by manual traction on cervical spondyloarthrosis.